Evolution of hematological parameters in hiv-1-infected patients with and without thalassemia carriages during highly active antiretroviral therapy - Sakorn Pornprasert (2018)
Objectives: To assess the effects of highly active antiretroviral therapy (HAART) on hematological parameters in HIV-1-infected patients with and without thalassemia carriages. Methods: Prospective study was conducted in HIV-1-infected Thai patients receiving HAART. Their hematological parameters were measured at baseline and during follow-up of 1 year. β-thalassemia and hemoglobin-E trait were diagnosed using HPLC. PCR-genotyping techniques were used to investigate α-thalassemia-1 Southeast Asian type deletion and β-thalassemia mutation. The changes of hematological parameters were compared according to thalassemia carriage. Results: During follow-up, increased levels of CD4 counts, hemoglobin, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) were observed in the groups of patients with and without thalassemia. The changes in mean hemoglobin level, MCV, and MCH in both groups appeared parallel, with consistently lower levels in patients with thalassemia. At Months 6 and 12, mean MCV of patients with thalassemia was shifted from microcytic levels (<80 fL) to normocytic levels (80-100 fL) while their mean MCH was increased to normal levels (27-31 pg). Conclusion: Although HAART altered hematological parameters such as MCV and MCH, it did not induce worsening anaemia, especially in patients with thalassemia carriages. However, the increased levels of MCV and MCH crucially affect the thalassemia screening. © 2009 Thomas Land Publishers, Inc.